The Impact of Persistent Irritability on the Medication Treatment of Paediatric Attention Deficit Hyperactivity Disorder - Baweja, Raman; Waschbusch, Daniel A.; Pelham, William E.; Pelham, William E.; Waxmonsky, James G. (Frontiers in Psychiatry, 2021)
This study compares the efficacy and tolerability of central nervous system (CNS) stimulants in children with attention deficit hyperactivity disorder (ADHD) with and without prominent irritability (IRR) over the course of 30 months. This is a secondary analysis of a study examining growth patterns in medication naïve children with ADHD subsequently treated with CNS stimulants (predominantly OROS-Methylphenidate, up to 54mg per day) for 30 months. Participants had to meet full diagnostic criteria for ADHD and been treated with CNS stimulants for under 30 days. Children were classified as IRR if they were rated as pretty much or very much on either of the “often angry” or easily annoyed” items plus “lose temper”, items of the Disruptive Behavior Disorders Rating Scale. Structured ratings of ADHD symptoms, impairment, side effects and symptoms of oppositional defiant disorder (ODD) were collected every 2-12 weeks for the duration of the study. Medication use was measured by pill count and parent report. The IRR group comprised 28% of all participants. The IRR group had significantly higher levels of ADHD and ODD symptoms, impairment and side effects ratings at baseline. In the IRR group, ODD symptoms, emotional lability and impairment significantly decreased for participants with higher medication use. Total side effects increased for non-IRR participants with higher medication use. Emotional side effects decreased for IRR participants with higher medication use. CNS stimulants were a tolerable and efficacious treatment in treatment naïve youth with ADHD with irritability.